Sea Surface Temperature Fronts and North Atlantic Right Whale Sightings in the Western Gulf of St. Lawrence - Jing Tao; Hui Shen; Richard E. Danielson; William Perrie (Journal of Marine Science and Engineering, 2025)
Sea surface temperature (SST) fronts during 2000–2021 are examined in the Western Gulf of St. Lawrence (wGSL), where North Atlantic right whales (NARW, Eubalaena glacialis) have begun to aggregate and feed. During 2017–2020, from May to October, NARW spatial distributions reveal regional, seasonal, and interannual variations in the Shediac Valley and off the Northern Gaspé Peninsula, and preferentially in waters with relatively strong temperature gradients. Correspondence between SST fronts and NARW sightings is explored using a monthly probability of occurrence, based on an SST gradient threshold and water depths in the range 50–200 m. Spring and summer associations suggest that satellite-derived SST gradients may aid in short-timescale NARW monitoring by way of providing spatial distribution maps of the regional probability of occurrence.